The life of reason in an age of terrorism - Padrón, Charles. (Value Inquiry Book Series, 2018)
With The Life of Reason in an Age of Terrorism , Charles Padrón and Kris Skowroński (editors) gather together a broad assortment of contributions that address the germaneness of George Santayana's (1863-1952) social and political thought to the world of the early twenty-first century in general, and specifically to the phenomenon of terrorism. The essays treat a broad range of philosophical and historical concerns: the life of reason, the philosophy of the everyday, fanaticism, liberalism, barbarism, egoism, and relativism. The essays reflect a wide range of viewpoints and perspectives, but all coalesce around discussions of how Santayana's thought fits in with and enhances an understanding of both our challenging times, and our uncertain future. Contributors are: Cayetano Estébanez, Matthew Caleb Flamm, Nóra Horváth, Jacquelyn Ann Kegley, Till Kinzel, Katarzyna Kremplewska, John Lachs, José Beltrán Llavador, Eduardo Mendieta, Daniel Moreno Moreno, Luka Nikolic, Charles Padrón, Giuseppe Patella, Daniel Pinkas, Herman Saatkamp, Jr., Matteo Santarelli, Krzysztof Piotr Skowroński and Andrés Tutor.